SYNTHESIS, CHARACTERIZATION, CYTOTOXICITY AND ANTIMICROBIAL STUDIES OF SCHIFF BASE DERIVED FROM 2-AMINOBENZOIC ACID AND BENZALDEHYDE AND ITS Cu(II) AND Zn(II) COMPLEXES - ADAMU, SAFIYANU LAME; SANI, UMAR; UMAR, ABDULLAHI BELLO; ROBA, BASHIR BELLO (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
A Schiff base ligand has been synthesized by the condensation of 2-aminobenzoic acid and benzaldehyde. Metal complexes of the Schiff base were prepared by the reaction of the Schiff base and metal (II) chlorides of copper and zinc in ethanol. The compounds were characterized by solubility test, melting point/decomposition temperature, molar conductance, magnetic susceptibility, FT-IR, metal-ligand ratio determination and UV-Visible Spectrophotometry. The Schiff base and metal(II) complexes were all soluble in DMSO, DMF, methanol, ethanol but insoluble in water and n-hexane. The IR spectra of the Schiff base showed a band at 1618cm-1 due to v(-C=N-) stretching vibration of the azomethine. This band shifted to lower frequencies of 1551cm-1 and 1543cm-1 respectively in the spectra of the metal (II) complexes. Conductivity measurement values indicated the non-electrolytic nature of the metal complexes. Job’s method of continuous variation suggests 1:2 Metal-ligand ratio. The in-vitro antibacterial activity carried out on Staphylococcus aureus, Streptococcus pnemoniae, E. coli and Klebsiela pnemoniaerevealed that the metal complexes exhibit higher activity than the Schiff base. The result for the antifungal screening revealed that the Schiff base and Zn (II) complex showed appreciable activity against Aspergillus fumigatus and Aspergillus flavus, the Schiff base and Cu (II) complex were found to be inactive at all concentration against Candida albicans. The cytotoxic results showed that the Schiff base and Zn (II) complex were highly-toxic with LC50 values of 63.191μ/mg and 76.684μ/mg while Cu (II) complex was non-toxic with LC50 of 1175.79μ/mg.